2018
DOI: 10.1002/anie.201712596
|View full text |Cite
|
Sign up to set email alerts
|

Polyvalent Display of Biomolecules on Live Cells

Abstract: Surface display of biomolecules on live cells offers new opportunities to treat human diseases and perform basic studies. Existing methods are primarily focused on monovalent functionalization, that is, the display of single biomolecules across the cell surface. Here we show that the surface of live cells can be functionalized to display polyvalent biomolecular structures through two-step reactions under physiological conditions. This polyvalent functionalization enables the cell surface to recognize the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 45 publications
3
62
0
Order By: Relevance
“…[197][198][199] Alternatively, DNA amphiphiles can be used to regulate cell-to-cell interactions through the anchoring of hydrophobic moieties and molecular hybridization of DNA. [200][201][202] In another work, Park et al reported that two amphiphilic block copolymers, poly(butadiene)-block-poly(ethylene oxide) (PBD-b-PEO) and polymethyl acrylate-block-DNA (PMA-b-DNA), could coassemble to form giant polymersomes ( Figure 20D); when two of this kind of polymersomes interacted via strand-hybridization, the DNA that originally uniformly distributed on the polymersome would gather to one side and form a DNA island. [195]…”
Section: Vesicle-dna Amphiphile Complexmentioning
confidence: 99%
“…[197][198][199] Alternatively, DNA amphiphiles can be used to regulate cell-to-cell interactions through the anchoring of hydrophobic moieties and molecular hybridization of DNA. [200][201][202] In another work, Park et al reported that two amphiphilic block copolymers, poly(butadiene)-block-poly(ethylene oxide) (PBD-b-PEO) and polymethyl acrylate-block-DNA (PMA-b-DNA), could coassemble to form giant polymersomes ( Figure 20D); when two of this kind of polymersomes interacted via strand-hybridization, the DNA that originally uniformly distributed on the polymersome would gather to one side and form a DNA island. [195]…”
Section: Vesicle-dna Amphiphile Complexmentioning
confidence: 99%
“…S1A †). [43][44][45] In order to restore more anchor ss-DNAs on cell surfaces, chlorpromazine (CPZ) was added into the medium to inhibit endocytosis (the cytotoxicity of CPZ toward Jurkat cells was also tested as shown in Fig. S1B †).…”
Section: Resultsmentioning
confidence: 99%
“…36 Recently, metabolic glycoengineering was used to label cell surface carbohydrates with DNA. 33,34 Lovendahl et al presented HUH-endonuclease domain fusion to covalently link DNA to proteins. 36 We attribute this rather scarce literature precedence to a lack of robust methods that allow conjugation without detriment to the protein function.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic glyco engineering 31,32 has been used to establish a covalent linkage between DNA and proteins on living cells, but this method does not allow tagging of specific proteins. 33,34…”
Section: Main Textmentioning
confidence: 99%